Designing creatures and characters : how to build an artist's portfolio for video games, film, animation, and more - Holmes, Marc Taro. (Cincinnati, Ohio : Impact Books, 2016)
"Ever wondered how you could become a character designer for video games, film or animation? Veteran art director and concept artist Marc Taro Holmes shares proven methods for honing the skills and building the portfolio necessary to become a pro gaming artist. This is the first and only work-at-your-own pace home study program that teaches the crucial insider knowledge needed to break into the entertainment-design industry and develop your own style--all you need are a pencil, paper and your imagination. The projects within this straightforward guide are constructed to help you apply your existing drawing and digital art skills to character design. Or, if you're still working on your skills, it will help you improve while at the same time turning your mind into an idea-generating machine"--Publisher's description.
What is this book all about? -- Who is it for? -- What is a concept artist? -- How can I get the most out of this course? -- Ho do the projects work? -- About achievements -- Why is the book designed this way? -- A note on individual style -- The design process -- Final preparation : the project brief.
Includes index.
Keywords: Characters and characteristics in art; Figure drawing -- Technique; Comic books, strips, etc. -- Technique; Animated films; Computer animation; Drawing -- Technique; Video game characters; Computer graphics; Computer drawing; Graphic arts -- Technique; Fantasy in art; Comic strip characters; Cartoon characters; Computer art; Graphic novels -- Technique; Graphic artists; Art portfolios